Isolasi dan Karakterisasi Senyawa Metabolit Sekunder Dari Kulit Batang Tumbuhan Niko (Grewia koordersiana Burret) - Klotilde Manek, Marliana; Landi Pote, Lodowik; Nadut, Anggelinus (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
Isolation and characterization of secondary metabolite compounds from the bark of the Niko plant (G. koordersiana Burret) aims to determine the type of secondary metabolite compounds and the characteristics of secondary metabolite compounds. The methods used are extraction, chromatography and spectrophotometry. A total of 500 g of Niko bark powder, macerated with methanol solvent, obtained a thick extract with a yield of 52.09%. The results of phytochemical tests showed that the methanol extract contained alkaloids, flavonoids, terpenoids and saponins. The results of fractionation by column chromatography using methanol eluent: ethyl acetate (1:3) obtained 20 fractions. The results of TLC for each fraction obtained 4 fractions with a single spot, namely fractions 11, 12, 15 and 16, where fractions 11 and 16 had Rf 0.3 and fractions 12 and 15 had Rf 0.7. Fraction A is fraction 11 and 16 with single spot concentrated and obtained extract of 2.09 grams (8.93%) and fraction B is fraction 12 and 15 obtained extract of 2.74 grams (11.53%). The results of characterization by UV-Vis spectrophotometry for fraction A obtained two absorption bands at wavelengths of 280 and 235 nm. Fraction B obtained two absorption bands at wavelengths of 280 and 245 nm. The results of the characterization using Infrared spectroscopy of methanol extract of Niko bark (G. koordersiana Burret) showed the presence of -OH groups at wave numbers 3383.14 cm-1 and aliphatic C-H groups (stretching) at wave numbers 2983.88 cm-1, carbonyl C=O groups at wave numbers 1741.72 cm-1, aliphatic C-H groups (bending) and alcohol C-O groups at wavelengths 1244.09, 1045.42 and 1033.85 cm-1. Based on the results of the UV-Vis and IR spectra, both isolates contain the same compounds.